Caracterização dos resíduos industriais gerados no processo de extração de óleos essenciais por arraste a vapor - Oliveira , Fabiane Cristina Martins de (2015)
The essential oil industry in Brazil is in full development, especially due to the researches conducted, thus expanding the knowledge of producers through relationships with universities. The extraction process by steam-dragging of essential oils is the most applied process in the industry of this segment, mainly because of its simplicity and low cost. Studies which involve this process have already gone beyond the knowledge of chemical composition, quality and applications. Currently, globalized world has the need for studies on the environmental variable for its survival, therefore this study aimed at analyzing the environmental impact caused by residues from the extraction process by steam-dragging of essential oils from aromatic plants, such as: Rosmarinus officinalis L., Piper hispidinervum C. CD., Pinus taeda L. e Pinus elliottii Engelm. The residues generated by the process are solid and effluent ones. Solid residues are only assessed as the mass generation; differently, the effluents were characterized by the analysis of environmental standards.Thus, it was possible to divide these analyzes by studying the following physicochemical parameters: pH, dissolved oxygen, chemical oxygen demand, biochemical oxygen demand, total organic carbon, color, turbidity, electrical conductivity, ammonia nitrogen, nitrate, nitrite, suspended solids, dissolved solids and total solids. The results indicate that the selected parameters of the analyzes of effluents generated in the extraction process by steam-dragging of essential oils of each one of the aromatic plants under study may be impactful for the environment in virtue of their values are not in accordance with those laid down in the environmental legislation in force.